2016
DOI: 10.5897/jeif2016.0743
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic variables and stock market performance of emerging countries

Abstract: This article seeks to fill the gap of severe data limitations on the link between macroeconomic variables and stock market performance. A panel data of 41 emerging countries for the period 1996 to 2011 was used to estimate the results. The model used by Sangmi and Mubasher (2013) was adopted and modified to determine the effect of macroeconomic variables on stock market capitalization. The four techniques to investigate the effects were robust ordinary least squares (OLS), FGLS, dynamic ordinary least squares … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The connection between securities exchange and loan fee is a mix of obligation and value financing. On the off chance that the pace of premium paid by banks to contributors is expanded, speculators will belittle the banks the more and less financial specialists will put resources into the securities exchange (Winful, Sarpong and Sarfo, 2016). This communication diminishes securities exchange execution just as the profitability of the economy.…”
Section: Interest Rate and Capital Market Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The connection between securities exchange and loan fee is a mix of obligation and value financing. On the off chance that the pace of premium paid by banks to contributors is expanded, speculators will belittle the banks the more and less financial specialists will put resources into the securities exchange (Winful, Sarpong and Sarfo, 2016). This communication diminishes securities exchange execution just as the profitability of the economy.…”
Section: Interest Rate and Capital Market Performancementioning
confidence: 99%
“…The results specified that the negative determinant was the money supply while economic growth, domestic credit and stock market liquidity showed positive effects on stock market development of the 36 emerging nations. Winful et al (2016) explored the effect of macroeconomic factors on financial exchange execution of 41 developing economies utilizing board information from 1996 to 2011. The investigation utilized four systems which include: common least squares (OLS) technique, dynamic standard least squares (DOLS), Newey-West and completely changed conventional least squares (FMOLS) estimators.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The link between stock market and interest rate is a blend of debt and equity financing. If the rate of interest paid by banks to depositors is increased, investors will patronize the banks the more and fewer investors will invest in the stock market (Winful, Sarpong & Sarfo, 2016). This interaction decreases stock market performance as well as the productivity of the economy.…”
Section: Interest Rate and Stock Market Performancementioning
confidence: 99%
“…The findings revealed that market index had a causal relationship with consumer price index, exchange rate, money supply and interest rate in Egypt while in Tunisia, it was only consumer price index that did not have causal relationship with the stock market index. Winful et al (2016) investigated the impact of macroeconomic variables on stock market performance of 41 emerging economies using panel data from 1996 to 2011. The study employed four techniques which include: ordinary least squares (OLS) method, dynamic ordinary least squares (DOLS), Newey-West and fully modified ordinary least squares (FMOLS) estimators.…”
Section: Empirical Reviewmentioning
confidence: 99%